Lasing in microcavities of fluorene-based polymer blends with liquid crystallinity - Lee, TW; Park, OO; Cho, HN; Kim, YC (ELSEVIER SCIENCE BV, 2003)
We report lasing characteristics of fluorene-based luminescent polymer blends with liquid crystallinity in a microcavity structure. Fluorene-based light-emitting polymers, poly(2,7-bis(p-stiryl)-9,9'-di-n-hexylfluorene sebacate) (PBSDHFS) and poly(9,9'-di-n-hexyl fluorenediylvinylene-alt-1,4-phenylenevinylene) (PDHFPPV), and a laser dye, 4(dicyanomethylene)-2-methyl-6-(p-dimethylaminostyryl)-4H-pyran (DCM) were used to comprise a binary or ternary blend system. We employed the Forster-type energy transfer from a liquid crystalline donor to a non-crystalline acceptor to obtain a low lasing threshold as well as to tune the color. The binary blend film of PBSDHFS/PDHFPPV (98/2 by wt.) demonstrated a very low-threshold energy (similar to3 nJ/cm(2)/pulse) for microcavity-lasing. We also observed a redshifed lasing from the PBSDHFS/PDHFPPV/DCM (98/2/2 by wt.) ternary blend device as a result of the cascade excitation energy transfer. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: AMPLIFIED SPONTANEOUS EMISSION; LIGHT-EMITTING-DIODES; ORGANIC THIN-FILMS; SEMICONDUCTING POLYMER; CONJUGATED POLYMERS; LASER; EFFICIENCY